Inflammatory factors and the risk of urolithiasis: a bidirectional Mendelian randomization study - Huang, Kunyuan; Peng, Zheng; Zha, Cheng; Li, Wei; Deng, Guanyun; Chen, Xiaolong; Luo, Yuting; Ji, Zhiqiang; Wang, Qing; Jiang, Kehua (Frontiers in Medicine, 2024)
Background: Urolithiasis is a prevalent condition encountered in urology. Although inflammatory factors are pivotal in the onset and progression of urolithiasis, their causal linkages remain elusive.Method: Mendelian randomization (MR) is predicated upon genome-wide association studies (GWASs). It integrates bioinformatics analyses to reveal causal relationships between exposures and outcomes, rendering it an effective method with minimized bias. Data from a GWAS meta-analysis of 8,293 samples identified 41 genetic variations related to inflammatory cytokines. Outcome data on upper (9,713 cases) and lower urinary tract stones (1,398 cases) were from the FinnGen Consortium R9 dataset. By leveraging the bidirectional MR methodology, we aimed to decipher the causal interplay between inflammatory markers and urolithiasis. Results: Post-MR analysis of the 41 genetic inflammation markers revealed that elevated levels of circulating interleukin-2 (IL-2) (OR = 0.921,95%CI = 0.848-0.999）suggest a reduced risk for renal stone disease, while heightened stem cell growth factor beta (SCGF-β) (OR = 1.150,95%CI = 1.009-1.310）and diminished macrophage inflammatory protein 1 beta (MIP-1β) (OR = 0.863,95%CI = 0.779-0.956）levels suggest an augmented risk for lower urinary tract stones. Furthermore, renal stone disease appeared to elevate IL-2 (β = 0.145,95% CI = 0.013-0.276) and cutaneous T cell-attracting chemokine (CTACK) (β = 0.145, 95% CI = 0.013-0.276) levels in the bloodstream, whereas lower urinary tract stones were linked to a surge in interleukin-5 (IL-5) (β = 0.142, 95% CI = 0.057-0.226), interleukin-7 (IL-7) (β = 0.108, 95% CI = 0.024-0.192), interleukin-8 (IL-8) (β = 0.127, 95% CI = 0.044-0.210), growth regulated oncogene alpha (GRO-α) (β = 0.086, 95% CI = 0.004-0.169), monokine induced by interferon-gamma (MIG) (β = 0.099, 95% CI = 0.008-0.191) and macrophage inflammatory protein 1 alpha (MIP-1α) (β = 0.126, 95% CI = 0.044-0.208) levels. Conclusion: These discoveries intimate the instrumental role of IL-2 in the onset and progression of upper urinary tract stones. SCGF-β and MIP-1β influence the development of lower urinary tract stones. Urolithiasis also impacts the expression of cytokines such as IL-2, CTACK, IL-5, IL-7, IL-8, GRO-α, MIG and MIP-1α. There is a pressing need for further investigation to ascertain whether these biomarkers can be harnessed to prevent or treat urolithiasis.